Penurunan E.Coli pada Air Lindi TPA Benowo Menggunakan Eco Enzim - Tilana, Cindy Marta; Widyastuti, Sri (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), Politeknik Negeri Cilacap, 2024)
Leachate with organic and inorganic content and heavy metals has the potential to pollute the environment. Therefore, alternative leachate treatment is needed. A complex organic liquid called eco-enzyme is the end product of fermentation of organic matter, sugar, and water. This study aims to determine the level of efficiency of eco-enzyme dosage to reduce BOD, COD, and E.Coli content in Benowo landfill leachate water samples. The technique implemented in this study was to dissolve eco enzyme using doses of 13%, 16.7%, and 20% into a reactor containing 7 liters of leachate water. Analysis of BOD, COD, and E.Coli levels was conducted on the 7th, 14th, and 21st day of each treatment. The results showed that the eco enzyme was able to reduce E.Coli but could not reduce BOD and COD of leachate water. The highest E.Coli reduction occurred at a dose of 13% from a concentration of 35000 MPN/100 ml to 1600 MPN/100 ml (95%). The highest decrease in E.Coli occurred on the 21st day of observation from a concentration of 35000 MPN/100 ml to 1600 MPN/100 ml (95%).